2017
DOI: 10.1007/s00705-017-3603-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the neuraminidase genes from human influenza A viruses circulating in Iran from 2010 to 2015

Abstract: The ongoing evolution of influenza viruses and the detect of influenza viruses with reduced susceptibility to NAIs warrants continuous monitoring of the circulating strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…It has also been reported that mutation N248D may be related to oseltamivir resistance because N248 is located near the binding pocket (Figure ). This N44S mutation may change the antigenic properties of influenza viruses because of an increase in the number of glycosylation sites . The N200S mutation possessed by genetic group 6 may be related to immune evasion by the virus because the mutation is at the antibody recognition site .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that mutation N248D may be related to oseltamivir resistance because N248 is located near the binding pocket (Figure ). This N44S mutation may change the antigenic properties of influenza viruses because of an increase in the number of glycosylation sites . The N200S mutation possessed by genetic group 6 may be related to immune evasion by the virus because the mutation is at the antibody recognition site .…”
Section: Discussionmentioning
confidence: 99%
“…This N44S mutation may change the antigenic properties of influenza viruses because of an increase in the number of glycosylation sites. 33 The N200S mutation possessed by genetic group 6 may be related to immune evasion by the virus because the mutation is at the antibody recognition site. 34 The V264I and N270K mutations detected in subgroup 6B are located in the antigenic region of the NA, and these two mutations may change the antigenic properties as well.…”
mentioning
confidence: 99%
“…19 Moasser et al also showed that most cases occurred in February and March. 20 Gouya et al reported that influenza is on the rise in the second half of the year coinciding with the reopening of schools and universities. 21 Belderok et al showed that traveling has an effect on the epidemiology of influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Many viruses, such as the influenza virus, evolve faster than normal transmission, and phylogenetic techniques as an ideal and objective tool can be used for reconstructing spatio‐temporal dynamics and transmission history 6 . With respect to implementation of this method for viruses like influenza, there are a series of studies which had been conducted in Iran to analyze the genetic diversity and drug susceptibility of the NA gene expressed by influenza A/H1N1pdm09 and A/H3N2 viruses on national and subnational level, and also comparing HA and NA genes of three 2009 pandemic influenza A/H1N1 isolates with the vaccine strain and some strains from different countries 7–9 . In some other studies bioinformatics methods were used to define the prevalence library and to study the trend of changes in HA and NA sequences of type A H1N1 influenza viruses from 2006 to 2013 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…6 With respect to implementation of this method for viruses like influenza, there are a series of studies which had been conducted in Iran to analyze the genetic diversity and drug susceptibility of the NA gene expressed by influenza A/H1N1pdm09 and A/H3N2 viruses on national and subnational level, and also comparing HA and NA genes of three 2009 pandemic influenza A/H1N1 isolates with the vaccine strain and some strains from different countries. [7][8][9] In some other studies bioinformatics methods were used to define the prevalence library and to study the trend of changes in HA and NA sequences of type A H1N1 influenza viruses from 2006 to 2013. 10,11 Further phylogenetic analysis on the NS gene of A/H1N1 isolates revealed that all Iranian isolates, except the A/Tehran/SMO08/2015, were close to strains from continental countries of Asia and North America, with 99% identity.…”
mentioning
confidence: 99%